Qingdao - Zhang, Miao; Rasiah, Rajah (Elsevier, 2013)
Qingdao, a coastal city in China, is located in the south of Shandong Peninsular by the Yellow sea. Its strategic location as an important port in northeast China has given the city a glorious past. The city's urban development was flavoured with the German and Japanese architecture until it was recaptured in 1949. The liberalization of China since 1978 led to the launching of a series of preferential policy packages to spur foreign investment. Geographical proximity with South Korea and Japan helped generate strong economic synergies to drive the city's growth. This profile captures the historical, economic and infrastructure development before and after the spatial development and housing provisions were introduced. The paper finishes by addressing the sustainability and environmental challenges that the city is increasingly facing now. The data used is drawn mainly from secondary sources, but also considerably from interviews and formal communications with the relevant officials of the urban authorities in Qingdao. © 2012 Elsevier Ltd.